2020
DOI: 10.1186/s42234-020-00061-5
|View full text |Cite
|
Sign up to set email alerts
|

Immunity and the carotid body: implications for metabolic diseases

Abstract: Neuro-immune communication has gained enormous interest in recent years due to increasing knowledge of the way in which the brain coordinates functional alterations in inflammatory and autoimmune responses, and the mechanisms of neuron-immune cell interactions in the context of metabolic diseases such as obesity and type 2 diabetes. In this review, we will explain how this relationship between the nervous and immune system impacts the pro- and anti-inflammatory pathways with specific reference to the hypothala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 208 publications
(327 reference statements)
0
10
0
Order By: Relevance
“…Supporting this link between the CB, dysmetabolism, and OSA, several studies demonstrated that the CB has a key role in the control of peripheral insulin sensitivity and glucose homeostasis since: (1) CSN resection prevents and reverses insulin resistance, glucose intolerance and dyslipidemia, which are pathological dysmetabolic characteristics, in hypercaloric diet rats (Ribeiro et al, 2013;Sacramento et al, 2017Sacramento et al, , 2018; (2) CSN resection prevents and normalizes the overactivation of the sympathetic nervous system associated with the intake of hypercaloric diets in rats (Ribeiro et al, 2013;Sacramento et al, 2017;Cracchiolo et al, 2019); and (3) CB activity is increased in animal models of metabolic syndrome and diabetes (Ribeiro et al, 2013;Dos Santos et al, 2018;Cracchiolo et al, 2019) and in prediabetic patients (Cunha-Guimaraes et al, 2020). Also in agreement with the role of the CB as a metabolic sensor whose dysfunction is associated with dysmetabolic states, several data showed that CB activity is modulated by hormones such as insulin (Ribeiro et al, 2013;Cracchiolo et al, 2019) and leptin (Ribeiro et al, 2018;Caballero-Eraso et al, 2019), and also by inflammation [for a review see (Conde et al, 2020)] whose levels are known to be deregulated in OSA (Ryan et al, 2005;Da Rosa et al, 2012). So, it could be postulated that CIH, by acting directly on the CB or indirectly by altering insulin secretion from the pancreas or by increasing leptin production in the adipose tissue and inflammation, leads to an increase in CB chemosensitivity promoting dysmetabolism (Figure 2).…”
Section: Increased Carotid Body Chemosensitivitymentioning
confidence: 86%
“…Supporting this link between the CB, dysmetabolism, and OSA, several studies demonstrated that the CB has a key role in the control of peripheral insulin sensitivity and glucose homeostasis since: (1) CSN resection prevents and reverses insulin resistance, glucose intolerance and dyslipidemia, which are pathological dysmetabolic characteristics, in hypercaloric diet rats (Ribeiro et al, 2013;Sacramento et al, 2017Sacramento et al, , 2018; (2) CSN resection prevents and normalizes the overactivation of the sympathetic nervous system associated with the intake of hypercaloric diets in rats (Ribeiro et al, 2013;Sacramento et al, 2017;Cracchiolo et al, 2019); and (3) CB activity is increased in animal models of metabolic syndrome and diabetes (Ribeiro et al, 2013;Dos Santos et al, 2018;Cracchiolo et al, 2019) and in prediabetic patients (Cunha-Guimaraes et al, 2020). Also in agreement with the role of the CB as a metabolic sensor whose dysfunction is associated with dysmetabolic states, several data showed that CB activity is modulated by hormones such as insulin (Ribeiro et al, 2013;Cracchiolo et al, 2019) and leptin (Ribeiro et al, 2018;Caballero-Eraso et al, 2019), and also by inflammation [for a review see (Conde et al, 2020)] whose levels are known to be deregulated in OSA (Ryan et al, 2005;Da Rosa et al, 2012). So, it could be postulated that CIH, by acting directly on the CB or indirectly by altering insulin secretion from the pancreas or by increasing leptin production in the adipose tissue and inflammation, leads to an increase in CB chemosensitivity promoting dysmetabolism (Figure 2).…”
Section: Increased Carotid Body Chemosensitivitymentioning
confidence: 86%
“…The carotid bodies (CB's) glomus cells (type I) have long been known as the body's main O 2 sensors (Ortega-Sáenz and López-Barneo, 2020). In light of recent evidence, however, they are now appreciated for their ability to "sense and respond" to a variety of non-respiratory stimuli including angiotensin II, leptin, cytokines, insulin, and lactate (Conde et al, 2014(Conde et al, , 2020Torres-Torrelo et al, 2021). Their strategic location at the bifurcation of the common carotid arteries allows them to act as multimodal chemosensors and thus play multiple roles in homeostasis beyond respiratory control.…”
Section: Introductionmentioning
confidence: 99%
“…Silvia V. Conde from CEDOC, Nova Medical School presented the main findings of her research focused on the role of the carotid body (CB) in metabolism (Conde et al 2020 ). The CB is a polymodal sensory organ capable of detecting glucose, leptin, and insulin in the blood.…”
Section: Defining Circuitsmentioning
confidence: 99%
“…Specifically, electrical neurostimulation using a kHz-frequency has been shown to block CSN activity, which Dr. Conde reports can be overactive in certain metabolic diseases. Dr. Conde’s work identified a neural signature in the CSN and sympathetic nerve activity and suggested that these structures could be a target for personalized bioelectronic therapeutics to treat metabolic disease (Conde et al 2020 ; Sacramento et al 2018 ).…”
Section: Defining Circuitsmentioning
confidence: 99%